EVALUASI KEBIJAKAN TENTANG KERJASAMA DI UNIVERSITAS X - halilintar, masnur putra; saputra, trio (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2017)
The purpose of this research is to know how to evaluate policy about cooperation in X presenting university and make ideal format of cooperation, research method using descriptive approach, research is arranged as inductive research is searching and collecting existing data field with aim to know factors, form-elements, and a trait of phenomena. Data analysis through four stages of data processing, data presentation, and withdrawal. Result of research technique and technique. This is because there is no standard operating procedure (SOP). The attitude of the executor of the cooperation body has not been effective and the inter-organization must also coordinate in more depth.